192k views
0 votes
How do you simplify squats roots

User Alinoz
by
5.6k points

2 Answers

5 votes
You need to make the inside number as small as possible and use the communicative property to rewrite the expression
User IMCoins
by
6.0k points
6 votes
Something to know when simplifying square roots:


√(ab) = √(a) * √(b)

Knowing this, we can choose two factors where one of the factors is a perfect square.

Examples:


√(12) = √(4) * √(3) = 2√(3)

Notice in this example if we used the factors 2 and 6 we wouldn't be able to simplify the square root.


√(32) = √(16) * √(2) = 4√(2)

We could have also used the factors 4 and 8 because 4 is a perfect square.
User Jim Macaulay
by
6.0k points